1975
DOI: 10.1111/j.1755-3768.1975.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Relatives of Persons With Fibrillopathia Epitheliocapsularis (Pseudoexfoliation of the Lens Capsule)

Abstract: The frequency of fibrillopathy (pseudoexfoliation of the lens capsule) among relatives of persons with fibrillopathy was investigated. Among 203 relatives over the age of 40 years, belonging to 25 families, fibrillopathy was found in 19, or in almost 10%. The frequency was independent of whether the proband had capsular glaucoma or normal intraocular pressure. Capsular glaucoma occurred in five of the 19 relatives. The results suggest that fibrillopathy may occur as a dominant hereditary trait, but it may also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
13

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 9 publications
0
18
0
13
Order By: Relevance
“…The prevalence appears rather similar in those countries where mass screening or population based surveys have been conducted (Aasved 1969(Aasved , 1971Hiller et al 1982); however, racial differences (Forsius & Luukka 1973), and occurrence in cer-tain families (Forsius & Eriksson 1961;Tarkkanen 1962;Aasved 1969Aasved , 1975 have been recorded. The prevalence appears rather similar in those countries where mass screening or population based surveys have been conducted (Aasved 1969(Aasved , 1971Hiller et al 1982); however, racial differences (Forsius & Luukka 1973), and occurrence in cer-tain families (Forsius & Eriksson 1961;Tarkkanen 1962;Aasved 1969Aasved , 1975 have been recorded.…”
Section: Introductionmentioning
confidence: 88%
“…The prevalence appears rather similar in those countries where mass screening or population based surveys have been conducted (Aasved 1969(Aasved , 1971Hiller et al 1982); however, racial differences (Forsius & Luukka 1973), and occurrence in cer-tain families (Forsius & Eriksson 1961;Tarkkanen 1962;Aasved 1969Aasved , 1975 have been recorded. The prevalence appears rather similar in those countries where mass screening or population based surveys have been conducted (Aasved 1969(Aasved , 1971Hiller et al 1982); however, racial differences (Forsius & Luukka 1973), and occurrence in cer-tain families (Forsius & Eriksson 1961;Tarkkanen 1962;Aasved 1969Aasved , 1975 have been recorded.…”
Section: Introductionmentioning
confidence: 88%
“…In Iceland the prevalence is 17.7% in patients aged 70 to 79 years and reached up to 40.6% in patients aged above 80 [20] years. PXS was also found to be generally more prevalent in men than in women [21]; this gender association though is not always reproducible [20]. The incidence of PXS roughly doubles each decade of life after the age of 50 [22] years.…”
Section: Pxs Demographicsmentioning
confidence: 99%
“…A few studies (Tarkkanen 1962;Pohjanpelto & Hurskainen 1972;Aasved 1975;Damji et al 1999;Allingham et al 2001;Orr et al 2001) in families consisting of between two and four generations have been described. Depending upon the study material, different modes of inheritance have been suggested: autosomal dominant (Tarkkanen 1962;Aasved 1975;Orr et al 2001), autosomal recessive (Andersen et al 1997) and maternal transmissions such as X-linked, mitochondrial and autosomal inheritance with genomic imprinting (Damji et al 1999). The main problem for investigations of the genetic background of ES has been the late onset of ES, where previous generations are often deceased at the time when the current generation is manifesting exfoliative changes.…”
Section: Introductionmentioning
confidence: 99%